(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
The effect of plant height and density of vegetation cover(millet) on the efficacy and residual effect of Metarhizium acridumconidia (Green Muscle®) in controlling Desert Locusts was evaluated insemi-field conditions inside large cages of 2x2x1 m. A mixed populationof third (L3) and fourth (L4) instars of nymphs was used as target. Thestudy was organized in two trials, separately carried out according to theplants height: Trial I, on short vegetation (27-37 cm) and Trial II, on tallvegetation (73-93cm). In both trials, the insects were treated in twodifferent vegetation covers: low ( 10 %) and high ( 100 %). A dose rateof 2.5 x 1012 conidia/ha was used with two different application volumes:1 and 2 L/ha. The efficacy of the biopesticide was evaluated by mortalityrate of treated nymphs followed during two weeks. On the other hand,untreated nymphs released in cages with treated vegetation were used toevaluate the effect of residual conidia in the two different vegetationstates. No significant influence of vegetation cover on the efficacy ofMetarhizium was observed in short vegetation (p = 0.828) or in tallvegetation (p =0.334) when a volume rate of 1 lire per hectare was used.In high vegetation cover, the increase of the applied volume rate to 2 litersper hectare significantly improved mortality rate. Also, conidia were alivesix days after treatment with good effect on untreated nymphs released ontreated vegetation. For the same period, no residual effect was observed in